2016
DOI: 10.1016/j.psychres.2016.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Mental simulation and experience as determinants of performance expectancies in people with schizophrenia spectrum disorder

Abstract: HighlightsWe confirmed previous findings of both impaired mental simulation ability and reduced performance expectancies in people with schizophrenia compared to healthy controls.Experience with tasks, rather than the ability to simulate them, was associated with performance expectancies in people with schizophrenia.Interventions should target problem solving, goal setting or task initiation rather than beliefs about performance. *Highlights 1 AbstractPeople with schizophrenia demonstrate both impairment in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our findings support past research demonstrating that people who suffer from psychiatric disorders have difficulties in generating detailed episodic future thoughts (Huddy et al, 2016). Our findings align with Brown et al (2013) who found, with similar effect sizes observed, that participants with PTSD had difficulties visualising future events.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support past research demonstrating that people who suffer from psychiatric disorders have difficulties in generating detailed episodic future thoughts (Huddy et al, 2016). Our findings align with Brown et al (2013) who found, with similar effect sizes observed, that participants with PTSD had difficulties visualising future events.…”
Section: Discussionsupporting
confidence: 92%
“…The present investigation replicated and extended upon studies comparing the ability to generate future events between people with and without schizophrenia (Chen et al ., ; D'Argembeau et al ., ; de Oliveira et al ., ; Huddy, Drake, & Wykes, ; Raffard et al ., , ). People with schizophrenia were found to have a broad deficit in their ability to generate future events compared to healthy controls who did not have psychiatric diagnoses, with problems generating both positive and negative future events, compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The AI involves presenting cue words and eliciting possible events in a manner consistent with the AMT, but responses are coded in terms of the total number of episodic details that are provided by the respondent (for example, about time, place, perceptions, actions of the respondent or others), with higher scores indicating more detailed EFT. The remaining five studies used different forms of assessing EFT detail or specificity: one asked participants to generate future goals and then assessed which proportion were specific in nature (Dickson et al, 2013), one asked participants to solve possible future problems and rated the episodic detail in the answers (Huddy et al, 2016), one asked participants to simulate future events that would be selfdefining and provided specific parameters around this, such as the need for it be very familiar and evoke strong feelings (Raffard et al, 2016), one used a sentence completion task (Chen et al, 2016), and another involved participants generating plans about the future and related specific future events. Across the sample, the studies varied in terms of how many cues they provided to participants to elicit EFT, the valence of the cues, how far into the future the possible events were to take place, whether practice cues were administered, the time given to respond, the scoring methods, and the method of recording the responses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Given the established relationship between past and future thinking (e.g., Williams et al, 1996), it might be hypothesised that impairments in autobiographical memory found in psychiatric illness will also result in impairments in EFT. Indeed, some studies have shown that individuals with diagnosed psychiatric disorders have deficits in generating detailed and specific episodic future thoughts (e.g., Addis, Hach, & Tippett, 2016;Huddy, Drake, & Wykes, 2016), however, other studies have shown no effect (e.g., Kleim, Graham, Fihosy, Stott, & Ehlers, 2014;Raffard et al, 2016). Such differences in findings may be attributable to the different diagnostic groups under consideration, or methodological variation.…”
Section: Introductionmentioning
confidence: 99%